THE DESIGN OF EDUCATION EVALUATION SUBJECT USING GOOGLE CLASSROOM IN THE FACULTY OF TARBIYAH AND EDUCATION SCIENCE IAIN PALU - Erniati, Erniati (Jurnal Diskursus Islam, 2020)
This research is aimed to reveal how Google classroom is used in the education evaluation subject and the lecture design of education evaluation using Google Classroom in the major of Islamic Education Studies, faculty of Tarbiyah and Education Science, IAIN Palu. This research uses descriptive qualitative. It concludes that the education evaluation lecture using Google classroom gives benefit to the students as well as to the lecturer due to the direct and clear communication between them, especially the materials given by the lecturer. Google classroom makes the learning process delightful for the class becomes really fun and students can explore the materials more exceedingly.